2008
DOI: 10.1159/000167867
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Peritonitis in Patients on Continuous Ambulatory Peritoneal Dialysis: A Single-Centre Experience in India

Abstract: Aims: The clinical features, treatment and outcome of fungal peritonitis (FP) in continuous ambulatory peritoneal dialysis (CAPD) patients were examined. Methods: Dialysis records of all 303 end-stage renal disease (ESRD) patients initiated on CAPD treatment between January 1998 and February 2008 were reviewed retrospectively. Results: In the 303 patients dialysed between January 1998 and February 2008, a total of 137 bacterial peritonitis and 43 FP episodes were recorded. The incidence rate of FP was 0.67/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 14 publications
4
50
4
1
Order By: Relevance
“…The rate of fungal peritonitis is highly variable between countries, ranging from 1 to 15% [44,45,46,47]. However, in certain countries like India the rate can be as high as 14.3-23.9% [48,49]. Yeast, especially Candida species, dominated all fungal peritonitis.…”
Section: Issues Related To Peritoneal Dialysis In Asian Countriesmentioning
confidence: 99%
“…The rate of fungal peritonitis is highly variable between countries, ranging from 1 to 15% [44,45,46,47]. However, in certain countries like India the rate can be as high as 14.3-23.9% [48,49]. Yeast, especially Candida species, dominated all fungal peritonitis.…”
Section: Issues Related To Peritoneal Dialysis In Asian Countriesmentioning
confidence: 99%
“…[1] Indian studies have reported incidence of FP rates varying from 14.3%[13] to 23.88%, respectively. [14] In our study, FP accounted for 14% of all peritonitis episodes.…”
Section: Discussionmentioning
confidence: 61%
“…In an Indian study, fungal peritonitis accounted for 23.88% of all peritonitis episodes. 4 Three factors appeared to predict mortality: the presence of non-Candida species, the catheter being left in situ and a serum albumin level 53 g/dL. 4 As peritoneal biopsy is rarely done in clinical practice unless it is a protocol procedure, a significant proportion of information on morphology is unavailable to the treating physician to predict the outcome.…”
Section: Discussionmentioning
confidence: 99%